A comprehensive analysis of biomarkers associated with synovitis and chondrocyte apoptosis in osteoarthritis - Yang, Ling; Yu, Xueyuan; Liu, Meng; Cao, Yang (Frontiers in Immunology, 2023)
Osteoarthritis (OA) is a chronic disease with high morbidity and disability rates whose molecular mechanism remains unclear. This study sought to identify OA markers associated with synovitis and cartilage apoptosis by bioinformatics analysis. A total of five gene-expression profiles were selected from the Gene Expression Omnibus database. We combined the GEO with the GeneCards database and performed Gene Ontology and Kyoto Encyclopedia of Genes and Genome analyses; then, the least absolute shrinkage and selection operator (LASSO) algorithm was used to identify the characteristic genes, and a predictive risk score was established. We used the uniform manifold approximation and projection (UMAP) method to identify subtypes of OA patients, while the CytoHubba algorithm and GOSemSim R package were used to screen out hub genes. Next, an immunological assessment was performed using single-sample gene set enrichment analysis and CIBERSORTx. 56 OA-related differential genes were selected, and 10 characteristic genes were identified by the LASSO algorithm. OA samples were classified into 2 subtypes by UMAP, and the clustering results showed that the characteristic genes were significantly different between these groups, MYOC, CYP4B1, P2RY14, ADIPOQ, PLIN1, MFAP5, LYVE1 were highly expressed in cluster2, and ANKHLRC15, CEMIP, GPR88, CSN1S1, TAC1, SPP1 were highly expressed in cluster1. Protein-protein interaction network analysis showed that MMP9, COL1A, and IGF1 were high nodes, and the differential genes affected the IL-17 pathway and tumor necrosis factor pathway. The GOSemSim R package showed that ADIPOQ, COL1A, and SPP1 are closely related to the function of 31 hub genes. In addition, it was determined that mmp9 and Fos interact with multiple transcription factors, and the ssGSEA and CIBERSORTx algorithms revealed significant differences in immune infiltration between the two OA subtypes. Finally, a qPCR experiment was performed to explore the important genes in rat cartilage and synovium This is a provisional file, not the final typeset article tissues, the qPCR results showed that COL1A and IL-17A were both highly expressed in synovitis tissues and cartilage tissues of OA rats, consistent with the predicted results. In the future, common therapeutic targets might be found for simultaneous remission of both phenotypes of OA.